Analisis Kebutuhan Booklet pada Materi Sel dan Transpor Zat melalui Membran untuk Peserta Didik Fase F SMA - Narulita Farahani; Helendra Helendra (Lembaga Yasin AlSys, 2025)
The topic of cells and substance transport across membranes is a fundamental component of biology instruction for Phase F students, as outlined in the Kurikulum Merdeka. However, the abstract nature of the material—characterized by numerous scientific terms and the inability to be directly observed—often poses challenges for student comprehension. Additionally, limitations in instructional media and teaching materials further hinder the learning process. This study aims to analyze the need for developing a biology booklet as a teaching resource on cell structures and membrane transport mechanisms for Phase F senior high school students. The research employed a Research and Development (R&D) method using the Four-D development model, with the current focus on the define phase. The study involved both teachers and Phase F students, with data collected through questionnaires regarding biology learning experiences and interest in educational media. Descriptive-qualitative analysis was conducted to provide an overview of instructional material needs. The results indicate that although students exhibit a high interest in biology, many still struggle to understand the topic of cells and membrane transport. The majority of respondents expressed a need for a booklet as a learning medium to support concept comprehension through visual and systematic presentation. It can therefore be concluded that developing a booklet on this topic is a concrete necessity that may enhance the effectiveness of biology instruction in senior high schools.